100 years after Liepmann–Lesion correlates of diminished selection and application of familiar versus novel tools. (January 2022) - Stoll, Sarah E.M.; Finkel, Lisa; Buchmann, Ilka; Hassa, Thomas; Spiteri, Stefan; Liepert, Joachim; Randerath, Jennifer
Abstract: 100 years ago, Liepmann highlighted the role of left ventro-dorsal lesions for impairments in conceptual (rather ventral) and motor (more dorsal) related aspects of apraxia. Many studies thereafter attributed to an extended left fronto-temporo-parietal network. Yet, to date there are only few studies that looked at apraxic performance in the selection and application of familiar versus novel tools. In the current study we applied modern voxel-based lesion-symptom mapping (VLSM) to analyze neural correlates of impaired selection and application of familiar versus novel tools. 58 left (LBD) and 51 right brain damaged (RBD) stroke patients participated in the Novel Tools Test (NTT) and the Familiar Tools Test (FTT) of the Diagnostic Instrument for Limb Apraxia (DILA-S). We further assessed performance in control tasks, namely semantic knowledge (BOSU), visuo-spatial working memory (Corsi Block Tapping) and meaningless imitation of gestures (IML). Impaired tool use was most pronounced after LBD. Our VLSM results in the LBD group suggested that selection- versus application-related aspects of praxis and semantics of familiar versus novel tool use can be behaviorally and neuro-anatomically differentiated. For impairments in familiar tool tasks, the major focus of lesion maps was rather ventral while deficiencies in novel tool tasks went along with rather dorsal lesions. Affected selection processes were linked to rather anterior lesions, while impacted application processes went along with rather posterior lesion maps. In our study, particular tool selection processes were rather specific for familiar versus novel tools. Foci for lesion overlaps of experimental and control tasks were noticed ventrally for semantic knowledge and FTT, in fronto-parietal regions for working memory and NTT, and ventro-dorsally for imitation of meaningless gestures and the application of NTT and FTT. We visualized our current interpretation within a neuroanatomical model for apraxia of tool use.